Public Service Delivery in Nepal: A Case of Passport Distribution from Passport Department, Kathmandu - Shahi, Hari Bhakta (Innovative Research Journal, 2022)
Public service delivery is providing goods and services to the people. Public service delivery is provided to the people by creating institution, developing system and needs of the people. Government of Nepal (GoN) created different ministries, departments and agencies to provide public services to the citizen. To provide public service delivery GoN created policies, Act, rules and regulations. This study concern to passport distribution service delivery which is systematized through passport act, rules and regulation. Passport are distributed from DoP, 77 districts and 39 diplomatic mission. In the year 2010 to 2021 total number of passport distributed were 7,037,320 citizens in which 22.10 percent of were females, and 77.90 percent of were males. Thus male were more provided service delivery in terms of passport distribution. DoP 2021 showed that, total of 553258 passport were distributed in that year in which 162,954 passport have been applied and distributed from DOP, 298,367 were applied and distributed from the districts, and 91,937 were applied and distributed from the missions abroad. This showed that service delivery at district level are higher.